Elm Grove pedestrian and bicycle safety survey, 2011 - Trechter, David; Hadley, Shelly (My University, 2011)
The Public Safety Committee of the Elm Grove Board of Trustees wanted to measure public opinion about safety issues for walkers, bikers, and joggers/runners in the village.
i + 48 p.
Keywords: Waukesha County, Wisconsin; Waukesha County (Wis.); Village of Elm Grove; Elm Grove (Wis. : Village); Safety measures; Cyclists; Pedestrians; Cycling--Wisconsin--Public opinion; Pedestrian areas--Wisconsin--Public opinion